Safety and effectiveness of dementia care management in primary care - Baoum, Shada Omar; Al-Ibrahim, Azhar Mohammed; Alharthi, Mohammed Thabet; Almohamad, Asma Abdulkarim; Althobaiti, Abdullah Hamoud; Alsagr, Wadiah Hassan; Almuhaysin, Mahdi Ibrahim; Almuhaymizi, Talal Abdulaziz; Althobaiti, Sami Atiah; Al-Jehani, Rowaa Mohammed; Hakami, Tareq Mohammed (International Journal Of Community Medicine And Public Health, 2022)
Globally, dementia affects 47.5 million people, making it a significant health concern. The growing number of people with dementia is posing a challenge to the health care systems. Dementia is a complicated progressive syndrome which is characterized by impairment of cognition, changes in personality leading to impeded daily life activities. Dementia poses burden to patients, their families society and healthcare systems in context of cost and care. People with dementia need intense medical, nursing, psychological, and social support to slow the disease’s progression and retain autonomy and social inclusion. Primary care has been shown to be the first point of contact for patients with dementia (PWD), making it an appropriate setting for diagnosis, in-depth needs assessments, and the beginning of dementia-specific therapy and care. The majority of dementia patients are treated in primary care settings and deal with complex medical and psychological conditions. They also suffer from various comorbid diseases along with dementia and take numerous psychotropic medications, including anticholinergics. However, the primary care system frequently fails to recognize their dementia-related symptoms due to certain constraints including time and lack of resources. Hence, the primary care system has to be supported with a variety of resources, such as dementia care managers, access to and coordination with interdisciplinary dementia specialists, and a practical dementia screening and diagnostic procedure, in order to provide better care for these vulnerable patients. The purpose of this research is to review the available information about safety and effectiveness of dementia care management in primary care.